PENGARUH ETIKA PROFESI DAN KOMITMEN PROFESIONAL AUDITOR TERHADAP KINERJA AUDITOR DENGAN SKEPTISISME PROFESIONAL SEBAGAI PEMEDIASI - Priesty, Dewa Ayu Astina Dyah; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 20 No 2 (2017)DO - 10.24843/EJA.2017.v20.i02.p11, 2017)
The purpose of this study was to analyze the influence of professional ethics and professional commitment to the performance of the auditor's through professional skepticism in the public accounting firm in Bali. This research was conducted in all public accounting firm in Bali as many as seven offices located in Bali region in 2016 with 81 auditors as a sample by sample method saturated. The data collection is done by distributing questionnaires to 78 respondents who returned and three aborted through path analysis techniques. Based on the analysis, the variables professional ethics and professional commitment auditor positive effect on the performance of auditors in the public accounting firm in Bali. Variable professional skepticism positive effect on the performance of auditors in the public accounting firm in Bali. Professional skepticism is able to mediate professional ethics and professional commitment to the performance auditor auditor on Public Accounting Firm In Bali.
Keywords: Professional Ethics, Commitment Auditor Professional, Professional Skepticism And Performance Auditor